Characterization and heterologous expression of the neoabyssomicin/abyssomicin biosynthetic gene cluster from Streptomyces koyangensis SCSIO 5802 - Jiajia Tu; Siting Li; Jiang Chen; Yongxiang Song; Shaobin Fu; Jianhua Ju; Qinglian Li (Microbial Cell Factories, 2018)
Abstract Background The deep-sea-derived microbe Streptomyces koyangensis SCSIO 5802 produces neoabyssomicins A–B (1–2) and abyssomicins 2 (3) and 4 (4). Neoabyssomicin A (1) augments human immunodeficiency virus-1 (HIV-1) replication whereas abyssomicin 2 (3) selectively reactivates latent HIV and is also active against Gram-positive pathogens including methicillin-resistant Staphylococcus aureus (MRSA). Structurally, neoabyssomicins A–B constitute a new subtype within the abyssomicin family and feature unique structural traits characteristic of extremely interesting biosynthetic transformations. Results In this work, the biosynthetic gene cluster (BGC) for the neoabyssomicins and abyssomicins, composed of 28 opening reading frames, was identified in S. koyangensis SCSIO 5802, and its role in neoabyssomicin/abyssomicin biosynthesis was confirmed via gene inactivation and heterologous expression experiments. Bioinformatics and genomics analyses enabled us to propose a biosynthetic pathway for neoabyssomicin/abyssomicin biosynthesis. Similarly, a protective export system by which both types of compounds are secreted from the S. koyangensis producer was identified, as was a four-component ABC transporter-based import system central to neoabyssomicin/abyssomicin biosynthesis. Furthermore, two regulatory genes, abmI and abmH, were unambiguously shown to be positive regulators of neoabyssomicin/abyssomicin biosynthesis. Consistent with their roles as positive regulatory genes, the overexpression of abmI and abmH (independent of each other) was shown to improve neoabyssomicin/abyssomicin titers. Conclusions These studies provide new insight into the biosynthesis of the abyssomicin class of natural products, and highlight important exploitable features of its BGC for future efforts. Elucidation of the neoabyssomicin/abyssomicin BGC now enables combinatorial biosynthetic initiatives aimed at improving both the titers and pharmaceutical properties of these important natural products-based drug leads.